Frequency of Esotropia and its Management in Pediatric Age Group at CMH Quetta - Malik, Sarah Naveed; Masud, Hannan; Zamir, Quratulain (Pakistan Armed Forces Medical Journal, 2024)
Objective: To find the frequency of esotropia, its sub types and subsequent management carried out in pediatric age group presenting to a tertiary care hospital in Quetta. Study Design: Cross-sectional study. Place and Duration of Study: Ophthalmology Department, Tertiary Care Hospital, Quetta Pakistan, from Jul to Dec 2020. Methodology: Two hundred and forty patients were enrolled in the study with age 6 months to 13 years presenting with manifest or latent squint. Data was collected through consecutive sampling technique. A designed form for refraction and orthoptic assessment was used with complete ophthalmological examination on each visit. Diagnosis was made based on international definitions of strabismus and treatment was planned accordingly. Follow up was carried out to observe and analyze the effects of treatment in strabismus. Results: Among 240 patients with strabismus, 152 patients had esotropia. More common in males (n=88) and most common refractive error was hypermetropia (n=94). Out of these 32 had anisometropia and 47 had amblyopia. According to classification of esotropia, 34.2% of patients had fully accommodative esotropia and 13.2% patients had essential infantile esotropia. Combination of treatment modalities was used. 21 patients were prescribed executive bifocals. Patching for 2 hours daily during activity under observation was advised to patients with amblyopia. 36 patients had surgery and 14 patients were kept under observation. Conclusion: Our study concluded that esotropia was the most prevalent type of strabismus in pediatric age group at tertiary care hospital in Quetta with accommodative type being the most common which can successfully be......